Pengaruh Konsentrasi Rootone F dan Jenis Media Tanam terhadap Keberhasilan Setek Satu Ruas Panili (Vanilla planifolia Andrews) - I Putu Adhi Wiriyanatha; I Wayan Wiraatmaja; I Nyoman Gede Astawa (Fakultas Pertanian, Universitas Udayana, 2021)
Vanilla (Vanilla planifolia Andrews) is a plants that has fruit with high economic value. The purpose of this study was to determine the concentration of Rootone F, types of growing media, and their combination to increase the success of one segment propagation of vanilla. This research was conducted from December 2020 to March 2021, located in Melinggih Kelod Village, Payangan, Gianyar. This study used a factorial randomized block design (RBD). Factor I: concentration of Rootone F which consists of concentrations 0 ppm (R0), 750 ppm (R1), 1.500 ppm (R2), and 2.250 ppm (R3), factor II: type of planting medium consisting of soil (T), soil + husk charcoal (TA), soil + cocopeat (TC), and soil + compost (TK) which was repeated 3 times. The concentration of Rootone F 2.250 ppm caused the highest total dry weight (4,30 g) or 49,31% higher than the 0 ppm treatment. The type of planting media soil + compost media caused the highest total dry weight (4,06 g) or 28,07% higher than the soil treatment. The combination of 2.250 ppm Rootone F with soil media + compos caused the highest total fresh weight of 85,07 g or 95,20% higher than 0 ppm Rootone F with soil media.